Developing Interactive Multimedia in Learning Animal Among Early Childhood - Budi Pramono, Aji Joko; Ahmad, Samlan (Universitas Lancang Kuning, 2018)
Abstract This research aims to produce interactive multimedia in learning Animal among Early Childhood in terms of aspects of the material, learning aspects, aspects of the display and programming aspects. This research was conducted in Kindergarten RA Ternate, Dufa-dufa Ternate Norts Maluku by using the method of research and development (R & D). The developing model is using ADDIE. Stages in this study consisted of: (1) planning, (2) design and (3) development (4 )Implementation (5)Evaluation The results show the resulted product is a multimedia learning to recognize Animal for early childhood, multimedia products produced viable as a medium of learning recognize Animal based on validation by matter experts and media experts. Feasibility of products based validation matter experts with excellent assessment results (4.0), validation by expert assessment of media with very good results (4.0) and assessment by a child on a trial-one, small group testing and operational test with results very good.